AVES DE ISLA FUERTE Y TORTUGUILLA, DOS ISLAS DE LA PLATAFORMA CONTINENTAL DEL CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
Bird observations were made during five days between 2004 and 2006 on Isla Fuerte and Isla Tortuguilla, two continental shelf islands of the Colombian Caribbean coast. On both sites 83 species were recorded. Isla Fuerte is larger and has a more complex array of habitats, supporting a larger and more complete bird community. Noteworthy species and aspects on the conservation of these insular environments are discussed.